THE IMPACT OF ANTI-TUBERCULOSIS DRUG ADVERSE EFFECTS ON MEDICATION COMPLIANCE IN PATIENTS WITH TUBERCULOSIS IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Nabila, Annisa Hasna; Amelia, Dewi; Atmaja, Naufal Brian; Putri, Nadya Fierdini; Setiawan, Tristan; Ilmi, Primayanti Nurul (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2025)
Tuberculosis (TB) remains a major public health problem in Indonesia, with treatment success highly dependent on patients’ adherence to anti-tuberculosis drug regimens. However, adherence is often hindered by adverse drug reactions (ADR), including nausea, vomiting, gastrointestinal disturbances, loss of appetite, and other symptoms that discourage patients from completing therapy. This systematic literature review aimed to analyze the impact of ADR on medication adherence among TB patients in Indonesia. Literature searches were conducted in Google Scholar, PubMed, and ScienceDirect databases using predefined keywords, with inclusion criteria covering articles published between 2020 and 2025, written in English or Indonesian, full-text available, and focusing on the relationship between ADR and treatment adherence. From the 22 eligible studies reviewed, the majority reported a significant relationship between ADR and adherence, while several studies indicated no significant effect. The most frequently reported ADR were gastrointestinal disorders, headaches, joint pain, and skin reactions. In addition, psychosocial factors such as family support, knowledge, and patient attitudes were also identified as influencing adherence, with family support emerging as the most dominant factor. Overall, ADR were found to negatively affect adherence in many cases, potentially increasing the risk of multidrug-resistant TB. Strengthened patient education, proactive counseling, and closer monitoring from healthcare providers are recommended to improve adherence and treatment outcomes.